Exploring financial derivatives through Shariah principles: identifying parallels in Islamic jurisprudence and modern finance - Nasrun, Mohamad Ghazali; Md. Sawari, Mohd. Fuad; Ghalia, Bouhedda; Syed Jaafar Alhabshi, Syed Musa (Usuli Faqih Research Centre, 2025)
This paper analyzes the key features of financial derivatives and explores their compatibility with Shariah principles by comparing them with contracts in Islamic jurisprudence, such as salam, istisnā’, and wa’d. The study highlights how these Islamic contracts align with the underlying functions of conventional derivatives, while avoiding prohibited elements such as gharar, ribā, and qimār/maysir. It employs a qualitative, document-based analysis, using a doctrinal approach to assess the feasibility of adapting conventional derivative instruments within a Shariah-compliant framework. The findings indicate that while Islamic alternatives fulfill similar economic objectives, structural limitations remain in addressing the complexities of modern derivatives markets. This research contributes to the ongoing discourse on Islamic finance by assessing the potential for ethical financial instruments to meet global market demands. However, it notes that further innovation is necessary to address the flexibility required in contemporary financial transactions